ANALISIS JUMLAH PRODUKSI OPTIMAL DENGAN METODE ECONOMIC PRODUCTION QUANTITY (EPQ) PADA NUTSAFIR COOKIES LOMBOK - Desi Suryati; Baiq Salkiah (Journal of Innovation Research and Knowledge, 2024)
This research aims to determine (1) the calculation of optimal production at Nutsafir Cookies Lombok, (2) the determination of the optimal production amount utilizing the Economic Production Quantity (EPQ) method at Nutsafir Cookies Lombok, and (3) the impact of implementing the Economic Production Quantity (EPQ) method on the profit obtained by Nutsafir Cookies Lombok. This research is a type of descriptive quantitative study. Data were collected using interview and documentation methods, and analyzed using descriptive analysis techniques with a quantitative approach. The results of the research indicate that (1) the calculation of optimal production quantity Nutsafir Cookies Lombok is still based on the number of consumer orders plus 30% of the orders for inventory, with the optimal production quantity for Nutsafir Cookies Lombok in 2023 amounting to 795,016 packages with a total inventory cost of Rp. 82,429,650.00, (2) the optimal production quantity using the Economic Production Quantity (EPQ) method at Nutsafir Cookies Lombok is 737,556 packages, with an average inventory of 84,820 packages and a total inventory cost of Rp. 76,685,655.00, (3) the impact of implementing the Economic Production Quantity (EPQ) method on the profit obtained by Nutsafir Cookies Lombok is that the profit obtained by the company increased by Rp. 5,743,345.00 due to the decrease in total inventory costs after applying the optimal production quantity calculation using the Economic Production Quantity (EPQ) method